2017
DOI: 10.4103/0366-6999.213969
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Real-world Entecavir Therapy in Treatment-naïve Chronic Hepatitis B Patients

Abstract: Background:Entecavir (ETV) has been shown to be effective in randomized controlled trials in highly selected patients with hepatitis B virus (HBV) infection. This study aimed to evaluate the efficacy of ETV in chronic hepatitis B (CHB) patients in the real-world setting.Methods:A total of 233 treatment-naïve, CHB patients who received at least 12 months of ETV treatment were included in this retrospective study. Rates of virological response (VR), hepatitis B s antigen (HBsAg) loss, hepatitis B e antigen (HBeA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Our proteomic approach showed that the F13A concentration was decreased in the blood plasma of patients with B-ALL. This observation has also been documented in whole plasma by ELISA assay in a study by Shi and Wang, in which a decrease of F13A in patients with acute myeloid and lymphoblastic leukemia and in solid tumors was reported [19]. Normal lymphoid cells do not synthesize or contain any F13 subunits, while lymphoid cells in bone marrow samples derived from patients with acute leukemia F13A do.…”
Section: Discussionsupporting
confidence: 66%
“…Our proteomic approach showed that the F13A concentration was decreased in the blood plasma of patients with B-ALL. This observation has also been documented in whole plasma by ELISA assay in a study by Shi and Wang, in which a decrease of F13A in patients with acute myeloid and lymphoblastic leukemia and in solid tumors was reported [19]. Normal lymphoid cells do not synthesize or contain any F13 subunits, while lymphoid cells in bone marrow samples derived from patients with acute leukemia F13A do.…”
Section: Discussionsupporting
confidence: 66%
“…It showed significant difference in studies for patients with HBV, HCV, depression, and fever by meta-analysis. Despite this, levels of HBV DNA and HBeAg clearance for CHM formula granules were much lower than for antivirals [50] or interferon [51]. This is a similar finding for patients with HCV RNA and HCV RNA clearance levels for CHM formula granules were much lower than for antivirals [52].…”
Section: Discussionmentioning
confidence: 78%
“…To our knowledge, HBeAg‐positive patients with high baseline serum HBV DNA levels usually indicated high risk of poor response to NAs therapy 13‐19 . In a previous study, about 26.2% of patients treated with ETV resulted in PVR, and the baseline serum HBV DNA level was an independent risk factor for PVR 20 . Thus, high baseline HBV DNA level seemed to be one of the important factors related with PVR.…”
Section: Discussionmentioning
confidence: 92%